Testing the effectiveness of health risk messages : threat and efficacy processing / Thinavan Periyayya and Vincent Wee Eng Kim - Periyayya, Thinavan; Wee, Vincent Eng Kim (Research Management Institute (RMI), 2014)
This is a micro study of an on-going macro study of the different categories of fear appeals used in the on-going national anti-smoking campaign. A quasi-experimental design was used to study the respondents’ responses to the anti-smoking print advertisement campaign. Two types of advertisements were selected, one which depicted a social threat and the other a damaging health threat. Each type of advertisement was evaluated by two separate groups of participants. The evaluation was based on the extended parallel process model’s (EPPM) risk diagnosis scale. The social threat advertisement had a low fear and efficacy message while the health threat advertisement had a high fear and efficacy message. Findings showed that the social threat (low fear/efficacy) was able to make the respondents of the study take a preventive behavioural or danger control position to avoid the negative consequences. In comparison the damaging health threat (high fear/ efficacy) was found to move the participants to a fear control position or maladaptive behavioural position. The study supported the main predictions of the EPPM, and showed that the efficacy construct determined how the fear appeal was processed (danger control or fear control).